The Economics of Oil and Gas Supply in the Former Soviet Union - Aguilera, Roberto F. (Inderscience, 2012)
Supply costs curves for the Former Soviet Union (FSU) are constructed for conventional petroleum, which is defined as conventional oil, natural gas and natural gas liquids (NGL). The supply figures show how petroleum quantities vary with production costs over time. Five resource quality categories, distinguishable according to production costs, are used in the estimation. The quantities are allocated across the five categories in a fixed proportion in order to generate the supply cost curves. The role of annual productivity gains, i.e., technological progress, to the year 2030 is also included. Results indicate that petroleum in the FSU is abundant and can be produced economically. In addition, production costs are found to decrease further over time as technology advances. With appropriate energy policy, FSU petroleum resources should assist in meeting domestic and international energy demand.